Layanan Konseling dalam Mendeteksi dan Mengembangkan Kecerdasan Anak melalui Kegiatan Parenting di Taman Kanak-Kanak - Wiyani, Novan Ardy (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
The quality of human resources is fundamentally shaped by early childhood education. However, efforts to detect and develop children's intelligence are often hindered by teachers’ limitations and parents’ lack of understanding regarding multiple intelligences. This community service program aimed to provide counseling-based parenting sessions for parents at TK Ar-Rohman in Brebes, with the goal of enhancing their knowledge and skills in identifying and optimizing their children's cognitive potential. The method employed was service learning, comprising three phases: investigation, implementation, and reflection. The core activity involved a parenting session attended by 46 parents, which included presentations on brain development in early childhood, the theory of multiple intelligences, detection strategies using nativist and empiricist approaches, interactive discussions, and individual counseling services. The results revealed a significant improvement in parents’ understanding, high enthusiasm during discussions, and increased motivation to seek further consultation. This program not only strengthened science-based parenting literacy but also offered accessible counseling alternatives within early childhood institutions. Therefore, parenting programs integrated with counseling services are proven to be effective in empowering parents and reinforcing collaborative synergy between teachers and parents to support children's optimal development. Keywords: Parenting, Counseling Services, Intelligence Detection, Early Childhood Education, Teacher–Parent Collaboration Kualitas sumber daya manusia sangat ditentukan oleh pendidikan sejak usia dini. Namun, deteksi dan pengembangan kecerdasan anak seringkali terkendala oleh keterbatasan guru serta rendahnya pemahaman orang tua terhadap ragam kecerdasan anak. Kegiatan pengabdian ini bertujuan memberikan layanan konseling melalui program parenting bagi wali murid di TK Ar-Rohman, Brebes, guna meningkatkan pengetahuan dan keterampilan mereka dalam mendeteksi serta mengoptimalkan kecerdasan anak usia dini. Metode yang digunakan adalah service learning yang melibatkan tiga tahap: investigasi, pelaksanaan, dan refleksi. Kegiatan utama berupa parenting session yang diikuti oleh 46 orang tua, meliputi penyampaian materi tentang perkembangan otak anak, teori kecerdasan majemuk, strategi deteksi berbasis nativisme dan empirisme, diskusi interaktif, serta layanan konseling individu. Hasil menunjukkan peningkatan pemahaman orang tua, antusiasme tinggi dalam sesi diskusi, dan munculnya inisiatif untuk berkonsultasi lebih lanjut secara personal. Program ini tidak hanya memperkuat literasi pengasuhan berbasis sains, tetapi juga menyediakan alternatif layanan konseling yang mudah diakses di tingkat PAUD. Dengan demikian, parenting berbasis konseling terbukti menjadi sarana efektif dalam memberdayakan orang tua serta memperkuat sinergi guru–orang tua dalam mendukung tumbuh kembang anak secara optimal. Kata kunci: Parenting, Layanan Konseling, Deteksi Kecerdasan Anak, PAUD, Sinergi Orang Tua–Guru